The Development of Supporting Video for English Textbook When English Rings a Bell of the Seventh Graders of Junior High School - Frida Unsiah; Putu Dian Danayanti Degeng; Irene Nany Kusumawardani (Journal of English Language Teaching and English Linguistics, 2016)
In accordance with Kurikulum 2013, teaching materials given to the classes have to reflect teaching activities in scientific approach. Dealing with it, it is important for teachers to provide interesting materials to attract students’ critical thinking. Thus, providing attractive and interactive media is also extremely necessary in order to create fun learning and maximal result for the students. However, appropriate media to support English textbook When English Rings a Bell for the seven graders of junior high school is not available yet. Therefore, it is urgently needed to develop it.Regarding with the absence of the media, this research was conducted with an aim to develop video using ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The result of the development, then, was assessed by an instructional design expert and was tried out by 4 English teachers from 2 public schools and 2 private schools of junior high in Malang city. The data were collected in the form of qualitative data employing questionnaire as the research instrument. To analyze the data, the researchers used descriptive qualitative analysis.Based on the result of the instructional expert’s assessment and teachers’ try out, it can be concluded that the video development as supporting media for English textbook When English Rings a Bell is considered good. Thus, it can be used by English teachers in classes.The research finding of video development is expected to be beneficial for English teachers as the supportive media of English textbook When English Rings a Bell for seven graders of junior high school. It is also expected to be beneficial for the seven graders of junior high school to increase their understanding on English materials of the textbook through the video.    Key words: video development, English textbook